Individual differences in behavioral reactions to H1N1 during a later stage of the epidemic - Ümmügülsüm Gaygısız; Esma Gaygısız; Türker Özkan; Timo Lajunen (Elsevier, 2012)
Summary: Previous studies regarding individuals' behavioral reactions to the H1N1 epidemic have been conducted nearly exclusively on the pre-pandemic phase of the epidemic or when the vaccine was not available. The prevalence and correlates of behavioral reactions to the H1N1 epidemic in Turkey were investigated by surveying 1045 respondents. The results indicate that behavioral responses can be divided into three classifications: recommended protective behaviors, avoidance behaviors, and ineffective behaviors. The frequency of recommended behaviors was higher than other behaviors, and respondents perceived these behaviors to be more effective. Recommended behaviors were predicted by the following factors: age, being female and married, the individual's beliefs in the effectiveness of the behavior, the perception that one's own behavior influences the infection risk, and the personality factors "Activity" and "Impulsive Sensation Seeking." Avoidance behaviors were predicted by the following factors: marital status, having small children, beliefs in the effectiveness of the behavior, mistrust of the government's ability to manage the epidemic, State Anxiety, and "Impulsive Sensation Seeking." Ineffective behaviors were predicted by the following factors: lower socio-economic status, marital status, the presence of chronic illness, the perceived effectiveness of the behavior, and State Anxiety. This study demonstrates that different types of behavioral reactions to the epidemic have different contributing factors and that these differences should be taken into account in public health interventions. Keywords: H1N1 epidemic, Protective behaviors, Avoidance, Individual differences, Turkey